A methods engineering study on Goldwin Manufacturing Laboratories Corporation - De Celis, Excel Ann (College of Engineering, 2000)
A methods engineering study is conducted on Goldwin Manufacturing Laboratories Corporation. GMLC is a corporation that produces skin care products. It is currently located in Marikina. With the use of Streamline Analysis Diagram, four problems are found : SCRAPS, INEFFICIENT MATERIAL HANDLING AND STORAGE (MSH), INEFFICIENT LAYOUT, and SLIPPERY FLOOR. Root causes of these problems are then found with the use of Ishikawa Diagrams. For the scraps, direct observation has prompted the group to verify the following as root causes for scraps : bulging of pans, carelessness in pouring solution, and spillage in the transport of raw materials. Flow process charts (FPC) and flow process diagrams (FPD) are used to verify the root causes of inefficiencies in MSH and layout. The root cause for the inefficiency in MSH is the improper positioning of the coconut oil. Improper positioning of the working tables, wrong position of the stamper, and the sealing section's placement in the first floor constitute the root causes for inefficient layout. Spills of soap solution in the mixing area and tailings in the cutting and packing section cause the slippery condition of the floor. Improved FPC's and FPD's, Cost-Benefit tables, and Systematic Layout Planning (SLP) Diagrams are used to arrive at the specified solutions. Solutions for the scraps include the use of wood frame, use of scraps as designs on transparent soaps, selling of scraps, and the implementation of the semi-boiled process. The semi-boiled process costs P11,603,982.00 and has a payback period of 8 years (see computations in the appendix section). It is noted that this figure and period are based on the 1994-1995 record of GMLC. Inefficiency in layout can be solved by the rearrangement of working tables, transfer of sealing section (with the shrinking machine) in the basement and the transfer of stamper to the side of pallet P (see Figure 32). Inefficient MSH is solved by the relocation of rack 3 (Figure 28), removal of rack 4's second rack level (Figure 29), and the marking with "full" and "empty" on the wall for coconut oil containers (Figure 30). Accidents due to slippery floor can be avoided by the provision of additional boots and the regular cleaning after work. A time study was conducted based on the present method of producing papaya soaps.